New regional industrial policy and environmental problems - G. I. Idziev; L. Sh. Akhmedova; P. A. Bekshokova; Z. V. Ataev (Юг России: экология, развитие, 2023)
Aim. The need to accelerate the transition to "green" and digital technologies leads to a more active participation of the state in the economy, including through an active industrial policy. In this regard, the main attention should be paid to the development and use of modern methodological approaches to the formation of a new regional industrial policy, taking into account the environmental aspect.Discussion. One of the main sources of pollutant emissions is industrial production. The article analyses the level of emissions of pollutants from industrial enterprises into the atmosphere in Russia as a whole, as well as for the regions that are leading in the growth of emissions into the atmosphere of industrial enterprises and in the growth in the number of polluting enterprises. Based on the analysis, it is concluded that in many regions of Russia industrial policy is carried out inefficiently. The growth of industrial production occurs extensively by increasing the number of enterprises or industries without taking into account environmental consequences and without the use of modern technologies that reduce the negative impact on the environment. An analysis of methodological approaches to the definition of the "new" industrial policy has been carried out and its general principles have been identified.Conclusion. To date, there is no clear definition of the "new" industrial policy, however, in modern scientific literature there are various methodological approaches that differ from the "old" type of industrial policy. The approaches discussed above differ in the emphasis either on the choice of specialisation – what to produce – or on the process by which prioritization and implementation occurs – how to produce.